Synergy of Islamic Religious Education and Legal Science: Building a Moral and Just Generation - Syarifah Salimah Nailulmuna; Dede Dwi Kurniasih; Yulia Nurmasita Devi; Khairatunni'mah SM; Hujjatul Fakhrurridha (Edumaspul: Jurnal Pendidikan, 2024)
This article discusses the importance of synergy between Islamic religious education and legal science in building a generation of morality and justice. In the context of a complex modern society, Islamic religious education not only functions as a character builder, but also as a moral foundation in understanding and applying the law. Through an interdisciplinary approach, this article examines how religious values can be integrated into the legal system, thus creating individuals who not only understand legal norms, but also have a high sense of ethics. By highlighting various examples of good practices and challenges faced, suggestions for an educational model that combines these two disciplines to produce a generation capable of contributing to social justice and better society development emerged. This article is expected to be a reference for educators, policymakers, and the general public in an effort to create a harmonious synergy between religious education and law.